The Effect of Cathode Materials on Indirect Electrochemical Oxidation of Methyl Orange, Malachite Green and Methylene Blue - Rao,Anantha N. S. (2014)
The influence of cathode material on the electrochemical degradation of methyl orange (MO), methylene blue (MB) and malachite green (MG) dyes was investigated. The cathode materials used were platinum (Pt), copper (Cu), zinc (Zn) and aluminum (Al). The electrochemical activity of the selected dyes on the metal cathodes was examined by cyclic voltammetry (CV). The electrochemical treatment was carried out in both divided and undivided cells. The degradation process was monitored by UV-Visible spectroscopy and chemical oxygen demand (COD) measurement. The influence of pH on discoloration and degradation of dyes was studied. The power consumption and current efficiency of the treatment process involving different cathode materials was computed and compared. The role of cathode material in the degradation of dyes has been established.